Effect of thyroid hormone replacement treatment on cardiac diastolic function in adult patients with subclinical hypothyroidism: a meta-analysis - Liu, Gejing; Ren, Man; Du, Yingshi; Zhao, Ruoyu; Wu, Yu; Liu, Yongming; Qi, Liang (Frontiers in Endocrinology, 2023)
Background: Although subclinical hypothyroidism (SCH) is related to abnormalities in left ventricular diastolic function, the use of levothyroxine as a regular treatment remains debatable. This meta-analysis aimed to determine whether thyroid hormone replacement therapy affects cardiac diastolic function in patients with SCH as measured by echocardiography.Methods: This meta-analysis included a search of the EMBASE, PubMed, Web of Science, and Cochrane Library databases from their inception to May 18, 2023, for studies analyzing cardiac morphology and functional changes in patients with SCH before and after thyroid hormone replacement. The outcome measures were cardiac morphology and diastolic and overall cardiac function, as assessed using ultrasound parameters (including ventricular wall thickness, chamber size, mitral wave flow, tissue Doppler, and speckle tracking). The quality of the studies was assessed using the Newcastle-Ottawa Scale. The standard mean differences (MDs) and 95% confidence intervals (CI) were calculated using fixed-or random-effects models.Results: Seventeen studies met the inclusion criteria. A total of 568 patients participated and completed the follow-up. All studies specifically stated that serum thyrotropin levels returned to normal by the end of the study period. Compared with baseline levels, no significant morphological changes were observed in the heart. In terms of diastolic function, we discovered that the ratios of E-velocity to A-velocity (E/A) had greatly improved after thyroid hormone replacement therapy, whereas the ratios of the mitral inflow E wave to the tissue Doppler e' wave (E/e') had not. Global longitudinal strain (GLS) increased significantly after treatment with levothyroxine.In adult patients with SCH, thyroid hormone supplementation can 2 partially but not completely improve parameters of diastolic function during the observation period.